2018
DOI: 10.5606/tgkdc.dergisi.2018.15083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of congenital heart surgery results: A comparison of four risk scoring systems

Abstract: Our study was presented as an oral presentation at the 15 th National Congress of Pediatric Cardiology and Cardiovascular Surgery. Prof. Dr. Aydın Aytaç Surgical Private was awarded

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Each variable has a reference value that was created by asking medical professionals to score each variable regarding their contribution to mortality, morbidity and difficulty on a scale from 1 to 5, and by computing the median of the scores. The Aristotle Comprehensive Complexity Score predicted 30-day mortality and length of ICU stay during the 1st postoperative week as well as morbidity after congenital heart surgery in previous studies (40,41).…”
Section: Aristotle Comprehensive Complexity Scorementioning
confidence: 90%
“…Each variable has a reference value that was created by asking medical professionals to score each variable regarding their contribution to mortality, morbidity and difficulty on a scale from 1 to 5, and by computing the median of the scores. The Aristotle Comprehensive Complexity Score predicted 30-day mortality and length of ICU stay during the 1st postoperative week as well as morbidity after congenital heart surgery in previous studies (40,41).…”
Section: Aristotle Comprehensive Complexity Scorementioning
confidence: 90%
“…In 2019, Bobillo-Perez et al [15] indicated that the predictive performance of the STAT score was better than that of the ABC score. [16] The controversial state of scoring systems in the adult group caused the search for a new scoring system. In their study published in 2015, Fuller et al [1] suggested that the ACHS mortality score was effective.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were some single center database studies, 22,23 this study is the first analysis of a multicenter registry in Turkey. The major contribution of the CKCV registry to the current practice is the real-time online reporting and self-analysis system.…”
Section: Discussionmentioning
confidence: 99%